Visual music instrument. (26th March 2009) - Dulic, Aleksandra; Hamel, Keith
Innovations in form and technology are fuelling the contemporary experimentation with musical, visual art and animation. The visual music expression through interactive computational media unites music, visual art and animation both in terms of their phenomenal experience and in terms of their elementary structure that consists of flexible and dynamic information flows and code. The flexibility and dynamism of coded processes readily support both performance and improvisation within interactive visual music and provides exciting compositional and expressive opportunities. In our visual music work, synaesthetic composition, computational expression and the dynamics of performance provide three elementary research axes.